Dates Consumption in Malaysia - Asmaddy Haris; Nurul Aini Muhamed; Nursilah Ahmad; Zurina Kefeli@ Zulkefli; Syadiyah Abdul Shukor; Aimi Fadzirul Kamarubahrin; Siti Nurazira Mohd Daud; Abu Hassan Makmun Abdul Qadir (Universiti Sains Islam Malaysia, 2024)
The aim of this study is to analyse and identify date consumption patterns by region in Malaysia. In addition, this study also will identify demand on dates in Malaysia. Currently, there is a lack of study on prophetic food, especially in Malaysia. The data were collected through survey questionnaires. The sample size of this study was 1739 respondents from various socioeconomic backgrounds, profession, and level of education. The survey was conducted in several states in Peninsular Malaysia in June 2015. Descriptive statistics and crosstab have been used to find the results. The findings showed that Selangor had the most date consumers. The reason is that Selangor is an urban state, and the level of income of respondents from this state is higher compared to other states. Moreover, the level of education and awareness among respondents in Selangor are better compared to other states. This study also showed that people tend to consume dates not only because of religion but also because of health factors. Findings of the study can be used to formulate and develop a systematic supply chain in the dates market.